TUMBUHKAN BUDAYA SOPAN SANTUN ANAK-ANAK MELALUI DIDIKAN SUBUH DI JORONG PANINJAUAN PASAMAN BARAT - Jenal Abidin; Sawaluddin Siregar; Auliya Citra (Yayasan Baitul Hikmah al-Zain, 2024)
One of the problems during community service is the decline in students' culture of politeness towards teachers. Politeness is the ancestral culture of this nation. This attitude really upholds the values ​​of respect for others in everyday life, the young respecting the old, and the old respecting the young. The loss of good manners for some students is one of the causes of lack of character formation. This is one of the impacts of the development of science and technology. If this is allowed to happen, it will have a negative impact on the future of the younger generation. This research was carried out when the researcher carried out community service based on PAR (Participatory Action Research). Data was collected through direct observation, interviews, field notes and documentation. The result of this community service is that through early morning education, children are more independent because they have their own responsibility to appear disciplined. Indirectly, children are also more disciplined in waking up early for morning prayers and then following the morning lessons. The implementation of the dawn education also had a positive impact, namely character education through exemplary stories of the Prophet's friends and Islamic fairy tales presented by KKL students.